Evaluasi Penerapan HELTI Menggunakan Metode Hot Fit Di Poltekkes Kemenkes Semarang - Isnaini Qoriatul Fadhilah; Nina Dwi Astuti; Puput Sugiarto (FORIKES, 2022)
During the online teaching and learning process, many obstacles are often encountered, such as users who do not understand how to use HELTI or the HELTI application is unstable if accessed by many users, causing the teaching and learning process to be disrupted. This study aims to determine the factors that influence the evaluation of the successful implementation of HELTI in Poltekkes Kemenkes Semarang. This type of research is analytic observational with a cross-sectional design. The subjects of this study were 228 students who were selected by simple random sampling technique. The dependent variable is the evaluation of the successful implementation of HELTI (net benefit), while the independent variables are technology, people, and organizations. Data were collected through filling out a questionnaire and then analyzed using logistic regression test. The results of the analysis show that technological factors, human factors, and organizational structure factors can increase the net benefit. A good technology factor can increase odd net profit by 1.30 units (OR=1.30, p= 0.001, 95% CI=1.10-1.54). Good human factor can increase odd net profit by 1.30 units (OR= 1.30, p= 0.06, 95% CI= 0.95-9.05). Good organizational structure management can increase odd net profit by 7.97 units (OR= 7.97, p= <0.001, 95% CI= 2.74-23.17). Facilities for improving e-learning applications are needed so that the effectiveness of learning can be carried out properly, especially when the application is accessed by many users.Keywords: HELTI; e-learning; HOT-FITABSTRAK Selama proses belajar mengajar secara online, banyak kendala yang sering ditemui, seperti pengguna yang tidak memahami cara menggunakan HELTI atau aplikasi HELTI tidak stabil jika diakses oleh banyak pengguna sehingga menyebabkan proses belajar mengajar terganggu. Penelitian ini bertujuan untuk mengetahui faktor-faktor yang mempengaruhi evaluasi keberhasilan penerapan HELTI di Poltekkes Kemenkes Semarang. Jenis penelitian ini adalah observasional analitik dengan desain cross-sectional. Subyek penelitian ini adalah 228 siswa yang dipilih dengan teknik simple random sampling. Variabel terikat adalah evaluasi keberhasilan penerapan HELTI (net benefit), sedangkan variabel bebas adalah teknologi, manusia, dan organisasi. Data dikumpulkan melalui pengisian kuesioner lalu dianalisis menggunakan uji regresi logistik. Hasil analisis menunjukkan bahwa faktor teknologi, faktor manusia, dan faktor struktur organisasi dapat meningkatkan net benefit. Faktor teknologi yang baik dapat meningkatkan keuntungan bersih ganjil sebesar 1,30 unit (OR=1,30, p= 0,001, 95% CI=1,10-1,54). Faktor manusia yang baik dapat meningkatkan keuntungan bersih ganjil sebesar 1,30 unit (OR= 1,30, p= 0,06, 95% CI= 0,95-9,05). Manajemen struktur organisasi yang baik dapat meningkatkan keuntungan bersih ganjil sebesar 7,97 unit (OR= 7,97, p= <0,001, 95% CI= 2,74-23,17). Fasilitas penyempurnaan aplikasi e-learning dalam sangat dibutuhkan agar efektifitas pembelajaran dapat terlaksana dengan baik terutama ketika aplikasi tersebut banyak diakses oleh banyak pengguna.Kata kunci: HELTI; e-learning; HOT-FIT